PERANAN BANK DALAM PEMBERIAN JASA LAYANAN INKASO - Sihaloho, Maria; Gea, Iwan; Tobing, Ferdinan Lumban; Hutapea, Haris; Siallagan, Hamonangan; Hasugian, Christnova (Jurnal Ilmiah Wahana Pendidikan, 2024)
The role of banks in providing collection services is becoming increasingly important along with economic and trade developments. This is because financial transactions between regions or cities are increasing. Changes in consumer behavior also influence the development of collection services. Collection is a banking service in the collection process or financial institutions, to collect payments from debtors who have not paid off their obligations. The development of information and communication technology has had a significant impact on banking services, including Inkaso services. The research used is a qualitative method, with a case study approach. The data collection technique used in this research is literature study, so this writing aims to find out the role of banks in providing collection services. The results of this research show that the important role of banks in providing collection services is as a provider of financial services, provider of infrastructure and networks, and provider of certainty and security. Furthermore, the Bank has a role as an intermediary, namely the Bank acts as an intermediary between the customer giving the mandate and interested parties and as a guarantor, namely the Bank acts as a guarantor for the results of the collection of collection documents. One of the roles of banks in providing collection services is to improve banking services in the debt collection process at financial institutions and to collect payments from debtors to pay off their obligations.